Graphene oxide modified lignin-based phenolic resin composite material and preparation method thereof
Through the preparation method of graphene oxide modified lignin-based phenolic resin composite, the problems of low thermal stability and mechanical strength of lignin-based phenolic resin composite are solved, efficient thermal stability and mechanical performance improvement are achieved, and the improvement of high-efficiency thermal stability and mechanical properties are promoted. High-value utilization of biomass resources.
Patent Information
- Application Number
- CN202411553359.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-10
AI Technical Summary
The existing lignin-based phenolic resin composites have poor performance in thermal stability and mechanical strength and lack efficient preparation methods.
The preparation method of graphene oxide-modified lignin-based phenolic resin composite material is adopted to phenolic modification of lignin and graphene oxide through enzyme powder and phenol to form in situ polymerization, thereby improving the reactivity of lignin and graphene oxide. The compatibility of the phenolic resin enhances the thermal stability and mechanical strength.
It realizes the application of high-value lignin and the green synthesis of phenolic resins, improves the thermal stability and mechanical properties of composite materials, reduces the use of phenol, and the preparation process is simple and convenient.
Smart Images

Figure CN119285879A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a graphene oxide modified lignin-based phenolic resin composite material and a preparation method thereof, and belongs to the technical field of phenolic resins. Background Art
[0002] Phenolic resin (PF) is one of the earliest discovered and industrially produced synthetic resins. It has unique advantages such as heat resistance, corrosion resistance, friction resistance, high physical strength, and low cost. It can meet various usage requirements and is currently widely used in coatings, adhesives, machinery, automobiles, electrical appliances, and other fields. Common phenolic resins are obtained by polycondensation of phenol and formaldehyde. Since phenol and formaldehyde are both petrochemical products, their use consumes a large amount of non-renewable resources and also causes certain environmental pollution. Therefore, the development of renewable or partially recycled phenolic resin products is of great significance to the development of the phenolic resin industry.
[0003] Lignin (L) is a biomass resource second only to cellulose in nature, with an annual output of about 2 billion tons. L has the advantages of abundant resources, non-toxicity, low cost, renewable, and biodegradable, and has broad application prospects. However, due to its structural complexity, the difficulty of dispersing macromolecules, and the heterogeneity of physical and chemical properties, it has not yet been fully and effectively utilized.
[0004] L is a natural polyphenol compound with a three-dimensional network structure in terms of chemical structure. There are many phenolic hydroxyl groups and aldehyde groups in the structure, and it has abundant reaction sites. In order to improve the shortcomings of L such as complex structure and low reactivity, it needs to be activated and modified during use to enhance its reactivity. The main approaches include chemical modification methods such as hydroxymethylation, phenolation, demethoxylation, and lignin chemical degradation, as well as physical modification methods such as microwave treatment and biological fermentation. The above methods can effectively enhance the reactivity of lignin. However, the existing lignin-based phenolic resin composites (L / PF) often perform poorly in terms of thermal stability and mechanical strength. Therefore, how to take into account the high-value application of lignin and the thermal stability and mechanical properties of composites in the synthesis process of phenolic resin composites has far-reaching research significance.
[0005] Graphene oxide (GO) contains abundant oxygen-containing functional groups such as carboxyl, hydroxyl and epoxy groups, and has good interfacial affinity with polymer matrices. Therefore, it has shown broad application potential in the development of composite materials with good mechanical and heat resistance properties. However, graphene oxide has a strong tendency to aggregate on the surface of polymer matrices, which greatly hinders the performance of its enhanced properties and also restricts its application in phenolic resin modification.
[0006] In summary, there is currently a lack of efficient means to prepare lignin-based phenolic resin composites with good thermal stability and high mechanical strength. Summary of the invention
[0007] In view of the existing problems, the present invention provides a graphene oxide modified lignin-based phenolic resin composite material and a preparation method thereof. The lignin-based phenolic resin composite material is prepared by in-situ polymerization of lignin, graphene oxide, phenol and formaldehyde; in the synthesis process of phenolic resin, lignin partially replaces phenol, effectively reducing the use of phenol, promoting the high-value application of lignin and the "green" synthesis of phenolic resin; the graphene oxide used in the lignin-based phenolic resin is activated and modified by enzyme powder and phenol, and has good compatibility with the phenolic resin matrix, solving the problems of poor thermal stability and low mechanical strength of lignin-based phenolic resin, and has broad application prospects.
[0008] The technical solution of the present invention is as follows:
[0009] The present invention provides a method for preparing a graphene oxide modified lignin-based phenolic resin composite material, comprising the following steps:
[0010] S1, phenolization modification of lignin: phenolization treatment of lignin using enzyme powder and phenol, wherein the phenol is filtered and recovered for later use after the phenolization treatment of lignin;
[0011] S2, preparing activated graphene oxide: using enzyme powder and phenol recovered in step S1 to activate graphene oxide, wherein the phenol is filtered and recovered for standby use after the activation treatment of graphene oxide;
[0012] S3, preparing a lignin-based phenolic resin composite material: mixing the activated graphene oxide obtained in step S2, the phenol-modified lignin obtained in step S1, and the recovered phenol by mechanical stirring, and then dispersing and polymerizing the mixture in formaldehyde to obtain the lignin-based phenolic resin composite material.
[0013] Furthermore, the specific steps of phenolization modification of lignin in step S1 are as follows: stirring and dispersing lignin in water, adding enzyme powder thereto and stirring and reacting at 75°C for at least 2h; then adding phenol thereto and reacting at 80°C for at least 1h; filtering the reaction solution while hot to obtain a filtrate and a filtrate, washing and drying the filtrate to obtain the activated lignin; cooling the filtrate in an ice water bath, and recovering the phenol by filtration.
[0014] Furthermore, in step S1, the dosage of lignin in water is 0.025 g / mL; the dosage of enzyme powder is 0.01 g / mL; and the dosage of phenol in water is 0.025 g / mL.
[0015] Furthermore, the enzyme powder is BT-70 enzyme powder.
[0016] Furthermore, the specific steps of preparing activated graphene oxide described in step S2 are as follows: stirring and dispersing graphene oxide in water, adding enzyme powder and phenol thereto, stirring the reaction solution at 85° C. for at least 1 hour, filtering the reaction solution while hot to obtain a filtrate and a filtrate, washing and drying the filtrate to obtain activated graphene oxide; cooling the filtrate in an ice-water bath, and recovering the phenol by filtration.
[0017] Furthermore, in step S2, the dosage of graphene oxide in water is 0.01 g / mL; the dosage of enzyme powder is 0.02 g / mL; and the dosage of phenol in water is 0.02 g / mL.
[0018] Furthermore, the specific steps of preparing the lignin-based phenolic resin composite material in step S3 are as follows:
[0019] The activated graphene oxide was mixed with the recovered phenol by mechanical stirring at 86°C, and then cooled to 75°C, and the phenol-modified lignin was added thereto, and the mechanical stirring was continued;
[0020] After the mixture is cooled, formaldehyde is added to the mixture and stirred to disperse to obtain a dispersion; the dispersion is heated to 100°C, HCl is added thereto and stirred for at least 105 minutes, formaldehyde is added and the solution is adjusted to neutrality using a NaOH solution, and then a 1wt% NaOH solution as a catalyst is added, and the solution is reacted at 100°C for 1 hour to obtain the lignin-based phenolic resin composite material.
[0021] Furthermore, the mass of the phenol-modified lignin added in step S3 accounts for 10% of the mass of the added phenol.
[0022] Furthermore, the graphene oxide added in step S3 accounts for 0.2-1% of the mass of the added phenol.
[0023] Further, the mass / volume ratio between the mass of phenol added in step S3 and the total volume of formaldehyde added twice in step S3 is 0.44 g / mL.
[0024] The present invention also provides a graphene oxide modified lignin-based phenolic resin composite material prepared according to the method.
[0025] Different from the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention synthesizes graphene oxide-modified lignin-based phenolic resin through the steps of lignin phenolation, graphene oxide activation, and polymerization of lignin-based phenolic resin in sequence; in this process, a phenol group is introduced into the benzene ring side chain of the phenolated lignin, which effectively increases the content of phenolic hydroxyl groups, enhances the reaction activity of lignin and the substitution rate of phenol; the inserted graphene oxide can form a good load transfer with the phenolic resin matrix, and improves the thermal stability and mechanical strength of the phenolic resin; in addition, the phenol used in the steps of lignin phenolation and graphene oxide activation can be recycled and reused for many times, and the preparation process of the phenolic resin effectively reduces the use of phenol, effectively alleviates the problem of large-scale use of petrochemical product phenol in the current preparation process of phenolic resin, and promotes the high value and green utilization of biomass resources.
[0027] 2. The lignin and graphene oxide used in the present invention are both activated by enzyme powder, the macromolecular structure of lignin is effectively degraded, the activity of lignin in the polycondensation reaction is improved, and then the substitution of lignin for phenol in the preparation process of phenolic resin is realized, the rigid structure of graphene oxide is also fully softened, and it can form a better interface bonding with the phenolic resin, play a role in strengthening and toughening the phenolic resin, the compatibility of the two in phenol and formaldehyde is fully improved, the substitution rate of lignin for phenol in the prepared phenolic resin composite material is high, and the prepared composite material has good mechanical properties.
[0028] 3. In the prior art, the strengthening and toughening modification of phenolic resin by graphene oxide requires the dispersion of graphene oxide in the resin matrix with the aid of an organic solvent, and the residual organic solvent often has a significant effect on the performance of the obtained composite material. Different from the prior art, the graphene oxide of the present invention is modified by enzyme powder and phenol phenolization, and has good solubility in the phenolic resin matrix, which can effectively improve the thermal stability and mechanical properties of the phenolic resin composite material. At the same time, the present invention uses lignin, graphene oxide, phenol, and formaldehyde as basic components, and obtains a phenolic resin composite material through in-situ polymerization. The preparation process avoids the use of organic solvents and complex functional modifications. Therefore, the lignin-based phenolic resin obtained by the present invention is green, environmentally friendly, has high mechanical strength, good high-temperature stability, and a simple and convenient preparation method, and has broad development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Infrared spectra of lignin before and after phenolation.
[0030] Figure 2 FT-IR graph of 10% L / PF and 0.2wt%~1wt% GO / L / PF composite materials.
[0031] Figure 3This is the XRD diagram of 10% L / PF and 0.2wt%~1wt% GO / L / PF composite materials.
[0032] Figure 4 Surface scanning electron microscope images of 10% L / PF and 0.2wt% to 1wt% GO / L / PF composite materials, where Figure a is 10% L / PF; Figure b is 0.2wt% GO / L / PF; Figure c is 0.4wt% GO / L / PF; Figure d is 0.6wt% GO / L / PF; Figure e is 0.8wt% GO / L / PF; Figure f is 1wt% GO / L / PF.
[0033] Figure 5 This is the thermal gravimetric diagram of 10% L / PF and 0.2wt%~1wt% GO / L / PF composites.
[0034] Figure 6 This is the tensile strength of 10% L / PF and 0.2wt%~1wt% GO / L / PF composite materials. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with the accompanying drawings and preferred embodiments. The given embodiments are only for illustrating the present invention, rather than for limiting the scope of the present invention.
[0036] Unless otherwise specified, the materials, reagents, etc. used in the following examples can be obtained from commercial sources; the methods in the following examples are conventional methods unless otherwise specified.
[0037] Example 1
[0038] This embodiment provides a method for preparing a graphene oxide modified lignin-based phenolic resin composite material, comprising the following steps:
[0039] S1, phenol modified lignin: 0.5g lignin (L) was stirred and dispersed in 200mL water, 2g BT-70 enzyme powder was added thereto and stirred and reacted at 75°C for 2h; then 5g phenol was added thereto and condensed and refluxed at 80°C for 1h; the reaction solution was filtered while hot to obtain a filtrate and a filtrate, the filtrate was washed and dried to obtain the activated lignin; the filtrate was cooled in an ice water bath, and then filtered to recover phenol;
[0040] S2. Preparation of activated graphene oxide: 0.5 g of graphene oxide (GO) was dispersed in 50 mL of water by stirring, 1 g of enzyme powder and 1 g of recovered phenol were added thereto, and the reaction solution was stirred at 85° C. for 1 h using a mechanical stirrer; the reaction solution was filtered while hot to obtain a filtrate and a filtrate; wherein the filtrate was washed and dried to obtain activated graphene oxide; the filtrate was cooled in an ice-water bath and then filtered to recover phenol;
[0041] S3, preparation of lignin-based phenolic resin composite material: activated graphene oxide and recovered phenol were mechanically stirred for 2.5h at 86°C, and then cooled to 75°C, phenol-modified lignin was added, and mechanical stirring was continued for 1h, wherein the mass of the added phenol was 9.4g, the added graphene oxide accounted for 0.2% of the mass of phenol, and the added lignin accounted for 10% of the mass of phenol; when the mixture was cooled to 50°C, 17.5mL of formaldehyde was added to the mixture and dispersed and stirred for 30min, and then the dispersion was heated to 100°C, 1mL of HCl was added thereto and stirred for 105min, and then 8.8mL of formaldehyde was added and NaOH solution was added dropwise to adjust the solution to neutrality, and then 10mL of 1wt% NaOH solution as a catalyst was added thereto, and the solution was reacted at 100°C for 1h to obtain the lignin-based phenolic resin composite material, and the obtained material was named 0.2wt% GO / L / PF according to the mass ratio of the added graphene oxide to phenol.
[0042] Example 2
[0043] This embodiment provides a method for preparing a graphene oxide modified lignin-based phenolic resin composite material, which is different from Embodiment 1 in that:
[0044] The graphene oxide added in step S3 accounts for 0.4% of the mass of phenol, so the prepared material is named 0.4wt% GO / L / PF.
[0045] The preparation steps of phenolized modified lignin, activated graphene oxide, and lignin-based phenolic resin composite material are the same as those in Example 1 and will not be repeated here.
[0046] Example 3
[0047] This embodiment provides a method for preparing a graphene oxide modified lignin-based phenolic resin composite material, which is different from Embodiment 1 in that:
[0048] The graphene oxide added in step S3 accounts for 0.6% of the mass of phenol, so the prepared material is named 0.6wt% GO / L / PF.
[0049] The preparation steps of phenolized modified lignin, activated graphene oxide, and lignin-based phenolic resin composite material are the same as those in Example 1 and will not be repeated here.
[0050] Example 4
[0051] This embodiment provides a method for preparing a graphene oxide modified lignin-based phenolic resin composite material, which is different from Embodiment 1 in that:
[0052] The graphene oxide added in step S3 accounts for 0.8% of the mass of phenol, so the prepared material is named 0.8wt% GO / L / PF.
[0053] The preparation steps of phenolized modified lignin, activated graphene oxide, and lignin-based phenolic resin composite material are the same as those in Example 1 and will not be repeated here.
[0054] Example 5
[0055] This embodiment provides a method for preparing a graphene oxide modified lignin-based phenolic resin composite material, which is different from Embodiment 1 in that:
[0056] The graphene oxide added in step S3 accounts for 1% of the mass of phenol, so the prepared material is named 1wt% GO / L / PF.
[0057] The preparation steps of phenolized modified lignin, activated graphene oxide, and lignin-based phenolic resin composite material are the same as those in Example 1 and will not be repeated here.
[0058] Comparative Example 1
[0059] This comparative example provides a method for preparing a lignin-based phenolic resin composite material, comprising the following steps:
[0060] S1, phenol modified lignin: 0.5g lignin (L) was stirred and dispersed in 200mL water, 2g BT-70 enzyme powder was added thereto and stirred and reacted at 75°C for 2h; then 5g phenol was added thereto and condensed and refluxed at 80°C for 1h; the reaction solution was filtered while hot to obtain a filtrate and a filtrate, the filtrate was washed and dried to obtain the activated lignin; the filtrate was cooled in an ice water bath, and then filtered to recover phenol;
[0061] S2. Preparation of lignin-based phenolic resin composite materials: Phenol and phenol-modified lignin are mechanically stirred and mixed at 86°C, wherein the mass of the added phenol is 9.4g, and the added lignin accounts for 10% of the mass of the phenol; after the mixture is cooled, 17.5mL of formaldehyde is added to the mixture and stirred to disperse, and then the dispersion is heated to 100°C, 1mL of HCl is added thereto and stirred for 105min, and then 8.8mL of formaldehyde is added thereto and NaOH solution is added dropwise to adjust the solution to neutrality, and then 10mL of 1wt% NaOH solution as a catalyst is added thereto, and the solution is reacted at 100°C for 1h to obtain the lignin-based phenolic resin composite material. According to the mass proportion of the added lignin in the phenol, the obtained material is named 10% L / PF.
[0062] Performance Testing
[0063] In order to illustrate the structure, high temperature resistance and mechanical properties of the synthesized phenolic resin composite material, the following tests were performed:
[0064] (1) Infrared analysis of phenolic resin composites
[0065] Fourier transform infrared spectroscopy analysis: The samples were measured using a Nicolet IS10 Fourier transform infrared spectrometer from Thermo Fisher Scientific, USA. The samples were pressed into films using the bromination method and then scanned at room temperature. The wave number scanning range was 500 to 4000 cm -1 , resolution 0.4cm -1 .
[0066] The infrared spectra of lignin before and after phenolization are as follows: Figure 1 As shown. Untreated lignin (Untreated L) at 3444cm -1 The -OH stretching vibration absorption peak is shown at 2892 cm -1 and 989cm -1 Represent the characteristic peaks of CH and CO stretching vibration of methoxy, 1377cm -1 The CO bending vibration of the syringyl aromatic ring of lignin is represented at 1218 cm -1 represents the absorption characteristic peak of aliphatic -OH, while 1600cm -1 、1509cm -1 、1479cm -1 The characteristic peak of the benzene ring of lignin (L) did not change significantly after phenol treatment, indicating that the skeleton structure of the aromatic ring was not destroyed during the phenolization process. -1 The characteristic peak intensity at 759 cm-1 was significantly enhanced, which indicates that the phenolization modification increased the -OH content in lignin. -1 and 694cm -1 Two new absorption peaks appeared at the 40°C, which was due to the nucleophilic substitution reaction between the hydroxyl group of the lignin side chain and the ortho-para position of the phenol ring. The comprehensive infrared spectrum results showed that phenol successfully reacted with lignin to achieve the phenolic modification of lignin.
[0067] FT-IR spectra of 10% L / PF and L / GO / PF are shown in Figure 2As shown. The intensity of the characteristic peaks of the GO / L / PF composite material has changed significantly, indicating that the hydroxyl groups on the surface of GO have associated with the phenolic resin to form intermolecular hydrogen bonds, indicating that there is good interface contact between the two. A chemical bond is formed between GO and PF, which has good interface compatibility, allowing GO to be stably dispersed in the resin. The spectrum of GO / L / PF is basically consistent with that of 10% L / PF, and there is no obvious GO characteristic peak. This is because the amount of GO introduced is low, its characteristic peak is masked by the characteristic peak of PF, and no chemical reaction occurs between GO and PF.
[0068] (2) XRD test
[0069] The X-ray powder diffractometer D8AA25 produced by Bruker AXS GmbH of Germany was used for the measurement, with a scanning angle of 10° to 80° and a scanning speed of 0.1.
[0070] The XRD spectra of the composite materials are shown in Figure 3 As shown. A "bun peak" was observed at 19.68°, which was caused by the adjacent chain structure of the linear polymer, indicating that the product was an amorphous structure. Figure 3 In the figure, after adding GO, the characteristic absorption peak at 2θ=19.68° becomes smaller, and the diffraction peak becomes wider. This is because the distance between the graphite oxide layers becomes larger, and the size of the graphite flakes is reduced to a certain extent after the redox reaction with phenol and formaldehyde. It can be inferred that PF has a certain intercalation effect on GO, which is beneficial to the dispersion ability of GO in the process of synthesizing phenolic resin. In addition, no GO peak is observed in the figure, which may be due to the presence of phenol and formaldehyde during the polymerization process, and a small amount of GO is reduced to graphene.
[0071] (3) Surface morphology test
[0072] Figure 4 The SEM surface morphology images of 10% L / PF and 0.2wt%~1wt% GO / L / PF composites are shown. The entire composite is a continuous phase without a dispersed structure, indicating that GO and resin are well combined. Figure 4 (b-f) shows that the uniformly dispersed GO is distributed in the resin carbon matrix in a disordered wrinkle morphology and is relatively uniformly distributed. The resin is evenly distributed and tightly coated on the surface of the graphene wrinkles to form a three-dimensional network porous structure. This combination form may play a certain role in strengthening the skeleton.
[0073] (4) Thermogravimetric test (TG)
[0074] Thermal analysis: STA, 409PC synchronous thermal analyzer from NETZSCH, Germany, was used for the measurement, with a heating rate of 10°C / min and N2 atmosphere. The sample mass was controlled between 5 and 10 mg.
[0075] Figure 5 The effects of L substitution, GO addition, and in-situ polymerization of resin on the thermal properties of PF are shown in Table 1. Detailed data are shown in Table 1. It is observed that both L / PF and GO / L / PF composites have good thermal stability under nitrogen atmosphere. The thermogravimetric curve of the resin can be divided into two stages: the first stage is when the sample is below 350°C, mainly the removal of small molecular polymers and free water in PF, and the weight loss rate is low; the second stage is at 350-600°C, oxygen-containing functional groups such as methylene and diphenyl ether become weak links in thermal degradation, and are prone to breakage to release small molecules such as carbon dioxide, with a high weight loss rate. Above 600°C, the TG curve is relatively flat, indicating that the residual rate tends to be stable.
[0076] exist Figure 5 In the results, the addition amount of GO has a greater influence on the thermal decomposition of PF. Compared with 10% L / PF, when the GO content is lower than 1wt%, the thermal stability of L / GO / PF composites is improved to varying degrees. Among them, the residual carbon rate of the composite material with 0.2wt% GO at 1000℃ reached 64.87%, and the initial decomposition temperature Td5% reached 340℃. The reason may be that GO forms a three-dimensional network structure in the resin matrix, which has a certain barrier effect on oxygen and heat. The hydrogen bonding between the two restricts the movement of L / PF molecular segments during thermal decomposition, thereby improving the thermal stability and residual carbon rate of the composite material. In summary, the addition amount of GO has a greater influence on the thermal decomposition of PF, and the addition below 1wt% can enhance the thermal stability of phenolic resin.
[0077] Table 1 Thermal properties of GO / L / PF composites
[0078]
[0079] (5) Mechanical properties test
[0080] Mechanical properties analysis: Take a small amount of samples and use the ST-15YP flat plate vulcanizer from Guangdong Easy Company to press the samples into a dumbbell shape (100x 25x 2mm). Use the FBS-20KNW universal material tensile testing machine to measure the samples at a tensile rate of 5mm / min.
[0081] Young's modulus and tensile strength are important influencing factors in the study of polymer mechanical properties. Figure 6 The changes in tensile strength, Young's modulus and elongation at break of PF composites at different L and GO contents are shown in Table 2.
[0082] Table 2 Tensile strength and elongation at break of GO / L / PF composites
[0083]
[0084] When the mass fraction of GO is 0.2-1wt%, compared with pure PF and L / PF composites, it is found that the tensile strength increases first and then decreases with the GO content, and the elongation at break also changes similarly. When 0.4wt% GO is added, the tensile strength can reach a maximum of 27.767MPa, which is 3.22 times that of pure PF; when the GO content increases to 0.8wt%, although the mechanical properties of the composite continue to improve, the trend slows down. This shows that GO has an enhancing effect on PF. The reason is that GO itself has good mechanical properties, effective load transfer with PF, and strong hydrogen bond interaction between the two. In addition, the layered structure of GO can bend and deform when subjected to external force, which offsets the external force and improves the stability of the structure. However, when the GO content increases to 0.8wt%, the tensile strength drops to 10.686MPa, which may be due to poor dispersion and weakened interface interaction.
Claims
1. A method for preparing a graphene oxide modified lignin-based phenolic resin composite material, characterized in that: The steps include: S1, phenolization modification of lignin: phenolization treatment of lignin using enzyme powder and phenol, wherein the phenol is filtered and recovered for later use after the phenolization treatment of lignin; S2, preparing activated graphene oxide: using enzyme powder and phenol recovered in step S1 to activate graphene oxide, wherein the phenol is filtered and recovered for standby use after the activation treatment of graphene oxide; S3, preparing a lignin-based phenolic resin composite material: mixing the activated graphene oxide obtained in step S2, the phenol-modified lignin obtained in step S1, and the recovered phenol by mechanical stirring, and then dispersing and polymerizing the mixture in formaldehyde to obtain the lignin-based phenolic resin composite material.
2. The method for preparing the graphene oxide modified lignin-based phenolic resin composite material according to claim 1, characterized in that: The specific steps of the phenolization-modified lignin in step S1 are as follows: stirring and dispersing lignin in water, adding enzyme powder thereto and stirring at 75°C for at least 2h; then adding phenol thereto and reacting at 80°C for at least 1h; filtering the reaction solution while hot to obtain a filtrate and a filtrate, washing and drying the filtrate to obtain the phenolization-modified lignin; cooling the filtrate in an ice-water bath, filtering and recovering it to obtain phenol.
3. The method for preparing the graphene oxide modified lignin-based phenolic resin composite material according to claim 2, characterized in that: In step S1, the dosage of lignin in water is 0.025 g / mL; the dosage of enzyme powder is 0.01 g / mL; and the dosage of phenol in water is 0.025 g / mL.
4. The method for preparing the graphene oxide modified lignin-based phenolic resin composite material according to claim 1, characterized in that: The specific steps of preparing activated graphene oxide described in step S2 are as follows: stirring and dispersing graphene oxide in water, adding enzyme powder and phenol thereto, stirring the reaction solution at 85° C. for at least 1 hour, filtering the reaction solution while hot to obtain a filtrate and a filtrate, washing and drying the filtrate to obtain activated graphene oxide; cooling the filtrate in an ice water bath, and recovering the phenol by filtration.
5. The method for preparing the graphene oxide modified lignin-based phenolic resin composite material according to claim 3, characterized in that: In step S2, the dosage of graphene oxide in water is 0.01 g / mL; the dosage of enzyme powder is 0.02 g / mL; and the dosage of phenol in water is 0.02 g / mL.
6. The method for preparing the graphene oxide modified lignin-based phenolic resin composite material according to claim 1, characterized in that: The specific steps of preparing the lignin-based phenolic resin composite material in step S3 are as follows: The activated graphene oxide and the recovered phenol are mechanically stirred and mixed at 86°C, and then cooled to 75°C, and the phenol-modified lignin is added thereto, and the mechanical stirring and mixing is continued; after the mixture is cooled, formaldehyde is added to the mixture and stirred and dispersed to obtain a dispersion; the dispersion is heated to 100°C, HCl is added thereto and stirred for at least 105 minutes, and then formaldehyde is added and the solution is adjusted to neutrality using a NaOH solution, and then a 1wt% NaOH solution as a catalyst is added, and the solution is reacted at 100°C for 1 hour to obtain the lignin-based phenolic resin composite material.
7. The method for preparing the graphene oxide modified lignin-based phenolic resin composite material according to claim 6, characterized in that: The graphene oxide added in step S3 accounts for 0.2-1% of the mass of the added phenol.
8. The method for preparing the graphene oxide modified lignin-based phenolic resin composite material according to claim 6, characterized in that: The mass of the phenolized modified lignin added in step S3 accounts for 10% of the mass of the added phenol.
9. The method for preparing the graphene oxide modified lignin-based phenolic resin composite material according to claim 6, characterized in that: The mass / volume ratio between the mass of phenol added in step S3 and the total volume of formaldehyde added was 0.44 g / mL.
10. A graphene oxide modified lignin-based phenolic resin composite material, characterized in that: The lignin-based phenolic resin is prepared by the method according to any one of claims 1 to 9.